Acute lymphoblastic leukemia‐secreted miRNAs induce a proinflammatory microenvironment and promote the activation of hematopoietic progenitors. Issue 1 (8th June 2022) - Rios de los Rios, Jussara; Enciso, Jennifer; Vilchis‐Ordoñez, Armando; Vázquez‐Ramírez, Ricardo; Ramirez‐Ramirez, Dalia; Balandrán, Juan Carlos; Rodríguez‐Martínez, Aurora; Ruiz‐Tachiquín, Martha; Pompa‐Mera, Ericka; Mendoza, Luis; Pedraza‐Alva, Gustavo; Mayani, Hector; et al.
Abstract: Leukemogenesis is proposed to result from the continuous interplay between inducive bone marrow (BM) microenvironments and malignant precursor cells. Recent findings point toward an abnormal production of proinflammatory mediators within the BM from acute lymphoblastic leukemia (ALL) patients, although the mechanism underlying this phenomenon is uncertain. Here, we have identified 3 miRNAs, miR‐146a‐5p, miR‐181b‐5p, and miR‐199b‐3p, as potential candidates for TLR8 ligation, which are overexpressed in ALL and show agonist functional binding. When purified from ALL exosomes, they demonstrated their capacity of inducing cytokine production by both, hematopoietic and stromal BM cells. Of note, the exposure of BM cells from ALL patients to the proinflammatory milieu resulting from these miRNAs agonist activity revealed the proliferation of normal progenitors, while poor effects were recorded in the leukemic counterpart. The unconventional roles of the tumor‐secreted miRNAs as TLR8 agonist ligands may provide a novel mechanism contributing a tumor‐microenvironment feedback loop by switching on proinflammatory pathways that further activate normal hematopoietic precursors and support ALL progression. Secreted B‐ALL TLR8‐agonist miRNAs are involved in the promotion of proinflammatory microenvironments that target normal hematopoietic cells. B‐lineage ALL cells secrete exosomes containing miRNAs endowed with the ability of functionally binding TLR8 in hematopoietic and BM mesenchymal stromal cells. Upon TLR8 signaling, the activation of the NF‐kB pathway induces secretion of proinflammatory cytokines that, in turn, promotes cell proliferation in early hematopoietic cell populations, driving a tumor–microenvironment–hematopoietic activation feedback loop that may reduce the normal hematopoietic stem and progenitor cell compartment and facilitate cancer progression. Graphical Abstract: This work describes a novel mechanism of acute leukemia regulation mediated by tumor miRNAs driving a pro‐inflammatory microenvironment and hematopoietic cell activation by TLR signals